Predicting affect from phone features using discriminant analysis - Seva, Rosemary R. (Animo Repository, 2006)
There are many products that may be studied for their potential to engender emotion but this study focused on the design characteristics of cellular phones. This study aims to identify which features of a cellular phone are capable of discriminating the intensity of emotional experience during the evaluation process. Consumers can either experience intense positive or negative emotion or not be emotionally affected by the features of the product. Forty two subjects voluntarily participated in a field survey conducted in selected shopping malls in the Philippines. A questionnaire was designed to gather data during the field study. The first part of the questionnaire inquired about the type and intensity of pre-purchase affect that subjects felt while examining the product that attracted their attention during the shopping process. Data gathered from field survey imply that dimensinal features of cellular phones such as width, height to width ratio, and size of navigation button are good discriminating variables. Phones with smaller widths and smaller navigation buttons can evoke intense positive emotion. Keywords: affective product design, discriminant analysis, cellular phone design